Jhaṛera pākhī, Ḍirojio - Senagupta, Pallaba, 1940- (Pustaka Bipaṇi, 1979)
On the life and work of Henry Derozio, 1807-1831, Portuguese born Indian nationalist teacher of Hindu College, Calcutta, and poet; includes translation of some of his poems in Bengali.